1982
DOI: 10.1063/1.330421
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermophotovoltaic conversion efficiency

Abstract: The theory and the experiments on thermophotovoltaic (TPV) conversion are reported in this paper. The various parameters characterizing TPV systems are studied in order to provide design information for actual converters. Both the experimental results and theoretical calculations of TPV conversion efficiency are presented for comparison. They exhibit good agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This convection would excite high-temperature phonons in the semiconductor, suppressing the PV effect. 19 The heating of the PV medium by the thermal radiation of the emitter also results in the excitation of phonons. It is a harmful effect restricting the overall efficiency of the PV conversion.…”
Section: Prospectives Of Micro-gap Tpv Systems and Wire Metamatermentioning
confidence: 99%
“…This convection would excite high-temperature phonons in the semiconductor, suppressing the PV effect. 19 The heating of the PV medium by the thermal radiation of the emitter also results in the excitation of phonons. It is a harmful effect restricting the overall efficiency of the PV conversion.…”
Section: Prospectives Of Micro-gap Tpv Systems and Wire Metamatermentioning
confidence: 99%
“…Several studies have been devoted towards quantifying the performance limits of TPV energy conversion devices (Coutts and Ward, 1999;Coutts and Benner, 1995;Demichelis et al, 1982;Shi et al, 2001;Whale and Cravalho, 2002). Most of them focused on the thermodynamic limits of energy conversion with no spectral control based on the approach by Shockley and Quiesser (1961).…”
Section: Efficiency Of Tpv Systemsmentioning
confidence: 99%
“…Some of the photons incident on a TPV cell are lost due to the shadowing by the electrodes which further reduces the efficiency (Green, 1982). Absorption of photons by the electrodes, electrical interconnects, and other non-power producing areas of the TPV arrays are often referred to as parasitic absorption (Demichelis et al, 1982;Mahorter et al, 2003). In order to avoid the absorption, non-power producing areas of the TPV system need to be minimized or coated with a reflective material to recycle the energy back to the radiator.…”
Section: Efficiency Of Tpv Systemsmentioning
confidence: 99%
“…Until about 2013, the reported experimental system efficiencies, in which the input power has been directly measured, were around 1% (16)(17)(18)(22)(23)(24). Then, beginning with 2015, system_exp exceeding 5% started to appear in the literature (19)(20)(21) Si-MIM structure on a tungsten substrate for the emitter (26).…”
Section: Introductionmentioning
confidence: 99%
“…Until about 2013, the reported experimental system efficiencies, in which the input power has been directly measured, were around 1%. , Then, beginning with 2015, η system‑exp exceeding 5% started to appear in the literature. For example, Kohiyama et al have reported 5.1% for η system‑exp by employing a ∼1650 K hot Mo-MIM structure for the emitter and a GaSb PV cell with a λ Eg of 1.85 μm . Biermann et al have reported η system‑exp = 6.8% by employing a ∼1300 K hot Si-MIM structure on a tungsten substrate for the emitter and a InGaAsSb PV cell with a λ Eg of 2.2 μm .…”
mentioning
confidence: 99%